Influence of thermal intrusion on the Alum Shale from south central Sweden - Liu, Anji; Zheng, Xiaowei; Schovsbo, Niels H.; Luo, Qingyong; Zhong, Ningning; Sanei, Hamed (International journal of coal geology, 2024)
This study investigates the geochemical and petrological characteristics of solid bitumen in the DBH15/73 core from the Furongian (upper Cambrian) and Miaolingian (middle Cambrian) Alum Shale in Billingen, south central Sweden. At Billingen a > 30 m thick Permian diabase (dolerite sill) intruded approximately 100 m above the Alum Shale that promoting the formation of solid bitumen in the uppermost half of the Alum Shale due to enhanced heat flow. The bitumen has been classified into bituminite/diagenetic solid bitumen (DSB), initial-oil solid bitumen (IOSB), and primary-oil solid bitumen (POSB) based on their genesis, morphology and random solid bitumen reflectance (BRo). The Miaolingian shale, constituting the lower part of the Alum Shale, is immature and contains solely bituminite and DSB, with measured BRo ranging from 0.40% to 0.48%. In contrast, the Furongian shale exhibits enrichment in IOSB and POSB and range from marginally mature to peak oil generation with towards the top of the section. Characteristics of uneven heating is seen in the IOSB (BRo: 0.97–1.08%) including oxidation rims and abnormally high maturity surrounding fractures. The POSB (BRo: 0.63–2.01%) is present not only in the Alum Shale but also in the overlying Ordovician Latorp limestone and the underlying Kakeled Limestone Bed, and shows flow structures which is further evidence for migration. The abundance of POSB and IOSB is determined through maceral point counting, revealing POSB as the dominant bitumen type (1.54–7.13 vol%), while IOSB constitutes the minority (0.05–0.31 vol%) within the Furongian shale. This distribution suggests rapid thermal evolution of organic matter within the oil generation window. Additionally, a reduction in free hydrocarbons (Rock-Eval S1), potential hydrocarbons (Rock-Eval S2), and unexpectedly low Tmax was observed in the Furongian shale. Results indicate that hydrocarbon generation resulting from thermal intrusion contributes to the relatively low S2. Migration of POSB and generated oil to adjacent layers leads to the loss of S1, while the reduced Tmax may be attributed to high uranium content which weakens carbon chain bond energy. These anomalies result in an underestimation when evaluating thermal maturity and kerogen type conversion based on Rock Eval data alone. •Introduce multiphases of solid bitumen in Alum Shale from central Sweden.•Report the solid bitumen migration and its implication on geochemical parameters.•Propose a genetic model describing the genesis of solid bitumen that exposed to heat of diabase intrusion.